Comparison the Formation of Spark Corona Discharge between Tap and distilled Waters at Liquid Electrode System (Baghdad Science Journal, 2013)
In this paper, we studied the spark corona discharge in tap and distillited waters. The results show the shape of cone that generated on the tip of capillary tube is different with conductivity of liquids. The blue glow appears at the end of capillary tube and the drop extends into a cone. In addition, the conducitivity is affected on the relationship between the appearance of the blue glow discharge with the applied voltage. The size of the cone decreases with an increase in applied voltage. The cone diameter at the base of capillary tube oscillates with period approximately 1 Sec. this oscillates in the cone diameters is due to the change distance between the liquid electrode and the surface of liquid. The intensity of spark corona discharge that formed in tap water higher than that formed in distillited water. In addiation, when the applied voltage is 5 KV on distillted water, the drope extends into two cones while in tap water the drop extends into one cone. These contrast between two water types which under test (i.e. tap and distillited waters) is due to the differance in condictivity of water.